Influence of Thermal Treatments, Extraction Methods, and Storage Conditions on Lycopene Content of Foods - Meenakshi Pathak; Narashans Alok Sagar (Journal of Food Quality)
Lycopene is one of the main carotenoids in our daily diet. Fruit variety, environmental conditions, and maturity stage are the factors affecting the content of lycopene. Various processing techniques and extraction methods may also affect the level of lycopene in different food products, consequently changing the biological role of lycopene. The biological role of lycopene is to defend the tissues of tomatoes (conjugate bonds) and attract predators (red colour). Moreover, storage conditions also impact the lycopene content of fruits, vegetables, and their products. Efficient and novel technological interventions are required for stabilizing lycopene content during postharvest procedures, such as refrigeration, heating, extraction, and transportation. Therefore, the study of different crucial factors concerning the change in lycopene content is required. The present review explores the lycopene content of different food commodities and the effect of postharvest operations and processing techniques on lycopene content. It also highlights the storage impact on the concentration of lycopene which may be useful for future studies.